ECONOMIC PERSPECTIVES ON RESETTLEMENT AND REHABILITATION OF DISPLACED IN ODISHA - Sial, Manoj Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
This article documents the process of displacement, rehabilitation and post-rehabilitation phase of the Tribal families of Similipal forest. It articulates issues for rehabilitation and resettlement, such as the concept of ’good governance’ versus ’govern-mentality’ (the dominance of state over natural resources and lives of forest residents, especially tribals) for the betterment of the displaced families; the need to equip the stakeholders for change in the economy and income-generation activities through imparting skills, tools and know-how; the measures to minimise adverse changes in socio cultural relations due to their spatial movements; and the way to reduce their vulnerability and marginalisation due to lack of political clout in the post-displacement phase. The article emphasises that the state has to adopt a participatory approach for the desired development of the stakeholders, that is, the residents of sanctuaries, especially when it has to deal with tribes whose subsistence economy is pastoralism. This paper describes the process of relocation and rehabilitation of villages populated primarily by tribals in Mayurbhanj district of Odisha. It examines the rehabilitation package offered, the process followed for relocation and resettlement and the impact that this shift has had on the livelihood of the affected people. While the rehabilitation package and the general attitude of the agency that carried out the relocation has been a significant improvement over previous such experiences, the shift has nevertheless had a negative impact on the livelihood of the people.